SUN’IY INTELLEKT TEXNOLOGIYALARINING MENEJMENTDAGI QO‘LLANILISHI: |IMKONIYATLAR VA XAVFLAR - Abdufattoxova Hadichaxon (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article analyzes the use of artificial intelligence technologies in management systems, their role in improving efficiency, and their impact on corporate governance. The study highlights the advantages of optimizing human resource management, marketing, and operational processes through AI. The risks associated with the implementation of artificial intelligence are also examined. Uzbekistan’s digital economy strategy and government policies aimed at developing AI are analyzed, and recommendations are provided for the effective integration of AI technologies into management processes.